Positive electrode active material, positive electrode slurry, positive plate, battery and vehicle
By combining lithium manganese iron phosphate and lithium nickel-cobalt manganese iron phosphate in lithium manganese iron phosphate batteries and controlling their mass ratio, the problem of difficult to take into account in the existing technology is solved, and high energy density and high The comprehensive performance of the battery with safety performance is improved.
Patent Information
- Application Number
- CN202411458540.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While increasing the energy density of lithium manganese iron phosphate batteries, the prior art ignores the safety performance of the batteries, resulting in safety hazards.
By combining lithium manganese iron phosphate and lithium nickel cobalt manganese oxide as the positive electrode active material, and controlling its mass ratio within the range of (50-95): (5-50), the mass ratio of lithium nickel cobalt manganese oxide is ensured. No more than 50% to take into account high safety performance and high energy density.
It achieves high safety performance while also having high energy density, improving the overall performance of the battery and avoiding safety hazards.
Smart Images

Figure CN119447227A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material, a positive electrode slurry, a positive electrode sheet, a battery and a vehicle. Background Art
[0002] With the continuous advancement of battery technology, the energy density of lithium iron phosphate (LFP) has reached a bottleneck, and industry researchers have gradually turned their attention to lithium manganese iron phosphate (LMFP) materials. Lithium manganese iron phosphate has the same olivine structure as lithium iron phosphate, good structural stability, and can take into account the safety and cycle advantages of lithium iron phosphate. At the same time, because manganese is introduced into lithium manganese iron phosphate, its average discharge voltage can reach 3.6V, which has a relatively high energy density advantage over lithium iron phosphate. However, compared with ternary materials, the energy density advantage of lithium manganese iron phosphate still has a large disadvantage.
[0003] In the related art, in order to improve the comprehensive performance of the battery, lithium manganese iron phosphate and ternary materials are mixed. However, the mixing system in the related art is mainly considered to improve the energy density of the battery to achieve the purpose of reducing costs, ignoring the safety performance of the battery, resulting in the battery being unable to take into account both energy density and safety performance, causing safety hazards. Summary of the invention
[0004] The embodiments of the present application provide a positive electrode active material, a positive electrode slurry, a positive electrode sheet and a battery, which can take into account both energy density and safety performance and improve comprehensive performance.
[0005] In a first aspect, an embodiment of the present application provides a positive electrode active material, including lithium iron manganese phosphate and lithium nickel cobalt manganese oxide;
[0006] Wherein, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is (50-95): (5-50);
[0007] The chemical formula of lithium nickel cobalt manganese oxide is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1.
[0008] In some embodiments, the median particle size D50 of lithium manganese iron phosphate is 0.5 μm-5 μm, and the specific surface area is 14 m 2 / g-25m 2 / g.
[0009] In some embodiments, the median particle size D50 of lithium nickel cobalt manganese oxide is 4 μm-18 μm, and the specific surface area is 0.2 m 2 / g-1.5m 2 / g.
[0010] In some embodiments, the chemical formula of lithium manganese iron phosphate is LiMn 0.6 Fe 0.4 PO4;
[0011] And / or, the chemical formula of lithium nickel cobalt manganese oxide is LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2 and LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2.
[0012] In some embodiments, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is 90:10.
[0013] In some embodiments, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is 70:30.
[0014] In some embodiments, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is 50:50.
[0015] In a second aspect, an embodiment of the present application provides a positive electrode slurry, comprising the positive electrode active material as above.
[0016] In some embodiments, the positive electrode slurry further includes a positive electrode conductive agent, a positive electrode binder, and a positive electrode dispersant;
[0017] The mass ratio of the positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the positive electrode dispersant is (95-98): (0.5-2.5): (1-3): (0-1).
[0018] In some embodiments, the positive electrode conductive agent includes at least one of carbon nanotubes, graphene, and acetylene black;
[0019] And / or, the positive electrode binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid.
[0020] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a positive electrode foil and a positive electrode active layer coated on the positive electrode foil;
[0021] The positive electrode active layer is prepared by using the positive electrode slurry as described above, or the positive electrode active layer includes the positive electrode active material as described above.
[0022] In some embodiments, the positive electrode foil is a carbon-coated aluminum foil;
[0023] The carbon-coated aluminum foil comprises an aluminum foil and a carbon coating layer coated on the aluminum foil, wherein the thickness of the aluminum foil is 6 μm-20 μm, and the thickness of the carbon coating layer is greater than 0 μm and less than or equal to 1 μm.
[0024] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as described above.
[0025] In a fifth aspect, an embodiment of the present application provides a vehicle comprising the battery as described above.
[0026] Beneficial effects of the embodiments of the present application:
[0027] In the embodiment of the present application, the positive electrode active material includes lithium manganese iron phosphate and lithium nickel cobalt manganese oxide, and the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is (50-95): (5-50). The chemical formula of lithium nickel cobalt manganese oxide is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1. Lithium manganese iron phosphate has the same olivine crystal structure as lithium iron phosphate, with higher safety performance, but lower energy density than ternary materials. The chemical formula of lithium nickel cobalt manganese oxide in this application is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1, that is, in lithium nickel cobalt manganese oxide, the molar content of nickel element accounts for more than 60% of the total molar content of the three elements of nickel, cobalt and manganese, and has a high energy density. However, due to the high nickel content, there is a problem of poor thermal stability, which reduces its safety when used in batteries. The present application uses lithium manganese iron phosphate and lithium nickel cobalt manganese oxide as positive electrode active materials, and controls the mass ratio of the two within the range of (50-95): (5-50), so that when the positive electrode active material with a mass proportion of no more than 50% of the lithium nickel cobalt manganese oxide is applied to the battery, it can have high safety performance while having a high energy density, thereby improving the overall performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 is a thermal runaway test curve diagram of the lithium-ion battery in Example 2 of the present application;
[0030] Figure 2This is a thermal runaway test curve of the lithium-ion battery in Comparative Example 1;
[0031] Figure 3 This is a thermal runaway test curve diagram of the lithium-ion battery in Comparative Example 2;
[0032] Figure 4 It is a normal temperature rate discharge diagram of some embodiments and comparative examples of the present application. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0034] In a first aspect, an embodiment of the present application provides a positive electrode active material, including lithium manganese iron phosphate and lithium nickel cobalt manganese oxide. The mass ratio of lithium manganese iron phosphate (LMFP) to lithium nickel cobalt manganese oxide (NCM) is (50-95): (5-50). The chemical formula of lithium nickel cobalt manganese oxide is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1. Lithium manganese iron phosphate has the same olivine crystal structure as lithium iron phosphate, with higher safety performance, but lower energy density than ternary materials. The chemical formula of lithium nickel cobalt manganese oxide in the embodiment of the present application is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1, that is, in lithium nickel cobalt manganese oxide, the molar content of nickel element accounts for more than 60% of the total molar content of the three elements of nickel, cobalt and manganese, and has a high energy density. However, due to the high nickel content, there is a problem of poor thermal stability, which reduces its safety when used in batteries. The embodiment of the present application uses lithium manganese iron phosphate and lithium nickel cobalt manganese oxide as positive electrode active materials, and controls the mass ratio of the two within the range of (50-95): (5-50), so that when the positive electrode active material is applied to the battery, it can have high safety performance and high energy density, thereby improving the overall performance.
[0035] Specifically, lithium manganese iron phosphate (LMFP) has the same olivine crystal structure as lithium iron phosphate (LFP), both of which are orthorhombic and belong to the Pnma space point group. The general chemical formula of lithium manganese iron phosphate is LiMn x Fe(1-x) PO4, 0<x<1. Each LMFP unit cell is composed of 4 basic units, among which lithium (Li) and manganese (iron) [Mn(Fe)] are located at the 4a site and 4c site of the octahedron, respectively, forming deformed LiO6 and MnO6 (FeO6) octahedrons. In addition, phosphorus (P) and oxygen (O) form PO4 tetrahedrons, located at the 4c site of the tetrahedron. Since P and O form a high-strength PO covalent bond, it is difficult for O to escape from the crystal structure, so LMFP has relatively high safety performance. Ternary materials have the characteristics of high theoretical specific capacity (>250mAh / g) and high operating voltage (~3.65V), becoming the mainstream of high energy density positive electrode materials, but with the increase of nickel content in ternary materials, thermal stability will decrease. When the molar content of nickel in lithium nickel cobalt manganese oxide is above 60%, its safety performance when directly applied to batteries is poor. The present application compounds lithium iron manganese phosphate and high nickel nickel cobalt manganese oxide in a mass ratio of (50-95): (5-50), so that when the positive electrode active material is applied to batteries, it can have high safety performance and high energy density, thereby improving the overall performance.
[0036] For example, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide may be 95:5, 90:10, 80:20, 70:30, 60:40 or 50:50. The chemical formula of lithium nickel cobalt manganese oxide may be: LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.7 Co 0.2 Mn 0.1 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2 or LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0037] In some embodiments, the median particle size D50 of lithium manganese iron phosphate is 0.5 μm-5 μm, and the specific surface area is 14 m 2 / g-25m 2 / g. The particle size of lithium iron manganese phosphate affects its electrochemical and mechanical properties. Lithium iron manganese phosphate with a smaller particle size has a larger specific surface area and can provide more active sites, thereby accelerating the insertion and deinsertion reactions of lithium ions. And lithium iron manganese phosphate with a smaller particle size has a shorter ion diffusion path, which makes the lithium ions migrate more rapidly during the charge and discharge process, reduces the stress concentration and lattice distortion caused by long-term charge and discharge, and thus improves the structural stability of the material. However, if the particle size of lithium iron manganese phosphate is too small, it is easy to form agglomerates, which increases the difficulty of preparation, and easily leads to a decrease in the mechanical strength of the lithium iron manganese phosphate material, affecting its cycle life and stability. Therefore, in the embodiment of the present application, the median particle size D50 of lithium iron manganese phosphate is set to 0.5μm-5μm. The specific surface area of lithium iron manganese phosphate is related to its particle size. The larger the particle size, the smaller the specific surface area, and the smaller the particle size, the larger the specific surface area. Accordingly, in the embodiment of the present application, the specific surface area of lithium iron manganese phosphate is set to 14m 2 / g-25m 2 / g.
[0038] For example, the median particle size D50 of lithium manganese iron phosphate may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm;
[0039] For example, the specific surface area of lithium manganese iron phosphate is 14m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g or 25m 2 / g.
[0040] In some embodiments, the median particle size D50 of lithium nickel cobalt manganese oxide is 4 μm-18 μm, and the specific surface area is 0.2 m 2 / g-1.5m 2 / g. Similar to lithium manganese iron phosphate, the particle size of lithium nickel cobalt manganese oxide will also affect its electrochemical performance and cycle life. When lithium nickel cobalt manganese oxide is used in batteries, if the particle size of lithium nickel cobalt manganese oxide is too small, the side reactions will increase, reducing the safety of the battery. If the battery of lithium nickel cobalt manganese oxide is too large, the battery capacity may be low. By keeping the particle size of lithium nickel cobalt manganese oxide within a certain range, the charging and discharging efficiency and cycle life of the battery can be improved while ensuring safety.
[0041] For example, the median particle size D50 of lithium nickel cobalt manganese oxide may be 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm or 18 μm;
[0042] For example, the specific surface area of lithium nickel cobalt manganese oxide is 0.2 m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g or 1.5m 2 / g.
[0043] In some embodiments, the chemical formula of lithium manganese iron phosphate is LiMn 0.6 Fe 0.4 PO4.LiMn 0.6 Fe 0.4 The high manganese content in PO4 can bring higher energy density. Manganese can stabilize the structure of the material during the charge and discharge process, reduce lattice distortion and stress concentration, and thus extend the cycle life. In addition, a high manganese content also helps to improve the low temperature performance and safety performance of lithium manganese iron phosphate.
[0044] In some embodiments, the chemical formula of lithium nickel cobalt manganese oxide is LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2 and LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2. LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2 and LiNi 0.9 Co 0.05 Mn 0.05 The high nickel content in O2 can significantly improve the energy density of lithium nickel cobalt manganese oxide. Nickel has high activity during the charge and discharge process and can provide more capacity contribution. And the higher nickel content also helps to optimize the cycle stability and charge and discharge efficiency of lithium nickel cobalt manganese oxide. During the charge and discharge process, the activity of the nickel element makes the insertion and deinsertion of lithium ions easier, thereby reducing the structural changes and capacity decay of the material. The nickel element has good conductivity and can accelerate the transmission speed of electrons in the material, thereby shortening the charge and discharge time and improving the charge and discharge efficiency. In addition, the increase in the nickel content corresponds to a decrease in the cobalt element in lithium nickel cobalt manganese oxide, thereby reducing the cost of the material. Since cobalt is a rare and expensive metal element, the reserves of nickel are relatively abundant and the price is relatively low.
[0045] In some embodiments, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is 90: 10. The high addition ratio of lithium manganese iron phosphate ensures safety performance and significantly improves energy density compared to using only lithium manganese iron phosphate in the positive electrode active material.
[0046] In other embodiments, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is 70: 30. By increasing the addition ratio of lithium nickel cobalt manganese oxide, the energy density can be further improved while ensuring safety performance.
[0047] In other embodiments, the mass ratio of lithium manganese iron phosphate to lithium nickel cobalt manganese oxide is 50:50. Under this ratio, it can be ensured that there is no fire or explosion during thermal runaway, and the overcharge test can be passed. In addition, since the addition ratio of lithium nickel cobalt manganese oxide is further increased, the energy density can also be significantly improved.
[0048] In a second aspect, an embodiment of the present application provides a positive electrode slurry, comprising the positive electrode active material as above.
[0049] The positive electrode slurry provided in the embodiment of the present application has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.
[0050] In some embodiments, the positive electrode slurry also includes a positive electrode conductor, a positive electrode binder and a positive electrode dispersant. Among them, the mass ratio of the positive electrode active material, the positive electrode conductor, the positive electrode binder and the positive electrode dispersant is (95-98): (0.5-2.5): (1-3): (0-1). The positive electrode active material is a key component for storage and release in the battery. By setting a high proportion of the positive electrode active material, it helps to increase the energy density of the battery. Under the same volume or weight, the battery can store more electrical energy, thereby extending the service time. An appropriate amount of positive electrode conductor helps to form an effective conductive network, reduce the internal resistance of the battery, and increase the electron and ion transmission rate, thereby enhancing the charge and discharge performance of the battery. The positive electrode binder plays a key role in maintaining the structural integrity and stability of the positive electrode sheet. By controlling the addition ratio of the positive electrode binder within a suitable range, it can ensure that the positive electrode active material does not fall off under the expansion and contraction during the charge and discharge process, maintain the stability of the structure, and thus improve the cycle life and safety of the battery. Dispersants help improve the fluidity of the positive electrode slurry and ensure that the positive electrode active materials can be evenly distributed.
[0051] In some embodiments, the positive electrode conductive agent includes at least one of carbon nanotubes, graphene and acetylene black. Among them, carbon nanotubes have a high electrical conductivity, and using them as positive electrode conductive agents helps to reduce the internal resistance of the battery and improve the battery charging and discharging efficiency. And carbon nanotubes also have good mechanical strength and flexibility, can withstand the volume change of the positive electrode active material during the charging and discharging process of the battery, reduce the risk of particle fracture and structural damage of the positive electrode active material, thereby improving the cycle stability of the battery, and when carbon nanotubes are used as positive electrode conductive agents, the amount of addition can be reduced, which helps to increase the addition ratio of the positive electrode active material, thereby increasing the energy density of the battery. Graphene has a large specific surface area, which helps to form electrolyte storage gaps and increase the contact area between the positive electrode active material and the electrolyte, thereby enhancing the battery's charging and discharging efficiency. And graphene has excellent mechanical properties, which can improve the volume energy density of the positive electrode sheet, increase the bendability and peel strength of the positive electrode sheet, thereby improving the overall stability of the battery. In addition, graphene also has good thermal conductivity, which can reduce the thermal impedance of the battery and improve the thermal stability of the battery. Acetylene black has moderate thermal conductivity, low nitrogen cost, and good mechanical stability, which can inhibit material shedding and damage.
[0052] In a third aspect, an embodiment of the present application provides a positive electrode sheet, comprising a positive electrode foil and a positive electrode active layer coated on the positive electrode foil, wherein the positive electrode active layer is prepared using the positive electrode slurry as described above, or the positive electrode active layer comprises the positive electrode active material as described above.
[0053] The positive electrode sheet provided in the embodiment of the present application also has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.
[0054] In some embodiments, the positive electrode foil is a carbon-coated aluminum foil, which includes an aluminum foil and a carbon-coated layer coated on the aluminum foil, wherein the thickness of the aluminum foil is 6 μm-20 μm, and the thickness of the carbon-coated layer is greater than 0 μm and less than or equal to 1 μm.
[0055] The carbon-coated aluminum foil includes an aluminum foil and a carbon coating layer coated on the aluminum foil. The carbon coating layer can optimize the surface properties of the aluminum foil, so that the positive electrode slurry can be more tightly and evenly attached to the aluminum foil, reducing the ineffective space, thereby improving the energy density of the battery. The thickness of the aluminum foil is set between 6μm-20μm, which not only ensures sufficient mechanical strength, but also reduces the weight of the battery and improves the energy density of the battery. The thickness of the carbon coating layer is set within the range of greater than 0μm and less than or equal to 1μm, which is ultra-thin and uniform, and helps to improve the overall performance of the battery.
[0056] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid. Polyvinylidene fluoride (PVDF) has excellent chemical stability and corrosion resistance, ensuring reliability and safety during use. PVDF also has good high voltage resistance, can remain stable under higher voltage conditions, and is not oxidized or deteriorated. It has good solubility and dissolution rate, can be evenly dispersed on the surface of the positive electrode slurry and the positive electrode sheet, thereby forming a uniform bonding layer, and it has high flexibility and bonding force, which can reduce the shedding phenomenon of the positive electrode active material during repeated expansion and contraction. Polytetrafluoroethylene (PTFE) has excellent corrosion resistance, strong stability, and good high temperature stability, and can be used for a long time at high temperature without decomposition. Polyacrylic acid (PAA) has good adhesion and can be connected to some functional groups on the surface of the positive electrode active material through hydrogen bonds, thereby forming a stable bonding layer, which helps to prevent the shedding and pulverization of the positive electrode active material. PAA can also effectively inhibit the volume expansion of the positive electrode active material during the charge and discharge process, thereby extending the cycle life of the battery. In addition, PAA itself has a small volume expansion coefficient and a large thermal diffusion coefficient. Using it as a positive electrode binder makes the battery safer when used under high-power charging and discharging and high temperature.
[0057] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet as described above.
[0058] The battery provided in the embodiment of the present application also has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.
[0059] In some embodiments, the battery further includes a negative electrode sheet, an electrolyte, and a separator.
[0060] Among them, the negative electrode sheet includes a negative electrode foil, a negative electrode active material, a negative electrode conductive agent and a negative electrode binder. The negative electrode foil is copper foil or copper mesh with a thickness of 4μm-12μm. Copper foil and copper mesh have excellent conductivity and low resistivity, and can quickly conduct current in the battery. Using them as negative electrode foil can provide an efficient conductive channel for the insertion and extraction process of lithium ions, thereby improving the battery's charge and discharge efficiency and response speed. Copper foil and copper mesh have high mechanical strength, which can protect the internal structure of the battery and increase the stability and strength of the internal structure of the battery. By controlling the thickness of the negative electrode foil to 4μm-12μm, it can not only ensure its structural strength, but also increase the energy density of the battery by reducing the mass of the negative electrode foil.
[0061] The negative electrode conductive agent is at least one of carbon nanotubes, carbon black and acetylene black. The advantages of carbon nanotubes and acetylene black have been described in the positive electrode conductive agent, and their application in the negative electrode conductive agent has similar advantages, which will not be repeated here. Carbon black has good electrical conductivity, can improve the conductivity of the negative electrode sheet, reduce the internal resistance of the battery, and carbon black can be evenly dispersed in the negative electrode active material to form a conductive network, accelerate the electron transfer rate, and improve battery performance. By using carbon black as a negative electrode conductive agent, the conductivity can be significantly improved on the basis of a lower addition amount, which helps to increase the addition amount of negative electrode active materials in the negative electrode sheet. Carbon black also has excellent chemical and physical stability, low cost, and good compatibility with other materials.
[0062] The electrolyte includes an electrolyte, an organic solvent and an additive. The electrolyte is at least one of lithium hexafluorophosphate (LIPF6), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The organic solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), polycarbonate (PC) and ethyl methyl carbonate (EMC). The additive includes at least one of vinylene carbonate (VC), vinyl sulfate (DTD), methylene disulfonate (MMDS), lithium bis(oxalatoborate) (LiBOB) and 1,3-propane sultone (PS), and the additive content accounts for 0.2%-1.5% of the total mass of the electrolyte.
[0063] The diaphragm includes a base film and a diaphragm coating coated on the base film. The base film side material is polypropylene (PP) or polyethylene (PE). The material of the diaphragm coating includes at least one of aluminum oxide, boehmite, magnesium hydroxide and barium sulfate. The thickness of the base film is 5μm-16μm, the thickness of the diaphragm coating is 0.5μm-5μm, and the tensile strength of the diaphragm is greater than 200MPa.
[0064] In a fifth aspect, an embodiment of the present application provides a vehicle comprising the battery as described above.
[0065] The vehicle provided in the embodiment of the present application also has the beneficial effects of the above-mentioned positive electrode active material, which will not be described in detail here.
[0066] The following examples are further described in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on the conditions recommended by the manufacturer.
[0067] It should be noted that, except for the conditions stated in the embodiments and comparative examples, the conditions in the embodiments and comparative examples remain the same.
[0068] Example 1
[0069] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 90% LiMn 0.6 Fe 0.4 PO4 with 10% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0070] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 22 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 10 μm and the specific surface area is 0.8 m 2 / g.
[0071] Example 2
[0072] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 70% LiMn 0.6 Fe 0.4 PO4 with 30% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0073] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 22 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 10 μm and the specific surface area is 0.8 m 2 / g.
[0074] Example 3
[0075] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 50% LiMn 0.6 Fe 0.4 PO4 with 50% LiNi 0.8 Co 0.1Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0076] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 22 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 10 μm and the specific surface area is 0.8 m 2 / g.
[0077] Example 4
[0078] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 95% LiMn 0.6 Fe 0.4 PO4 with 5% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0079] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 3 μm and the specific surface area is 18 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 12 μm and the specific surface area is 0.7 m 2 / g.
[0080] Example 5
[0081] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 80% LiMn 0.6 Fe 0.4 PO4 with 20% LiNi 0.8 Co 0.1 Mn 0.1O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0082] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 0.8 μm and the specific surface area is 24 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 8 μm and the specific surface area is 1.3 m 2 / g.
[0083] Example 6
[0084] In this embodiment: In the positive electrode sheet, the positive electrode active material includes 60% LiMn 0.6 Fe 0.4 PO4 with 40% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0085] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 4 μm and the specific surface area is 15 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 6 μm and the specific surface area is 1.4 m 2 / g.
[0086] Comparative Example 1
[0087] In this comparative example: in the positive electrode sheet, the positive electrode active material only includes LiMn 0.6 Fe 0.4 PO4; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0088] Among them, LiMn 0.6 Fe0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 22 m 2 / g.
[0089] Comparative Example 2
[0090] In this comparative example: in the positive electrode sheet, the positive electrode active material includes 40% LiMn 0.6 Fe 0.4 PO4 with 60% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0091] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 22 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 10 μm and the specific surface area is 0.8 m 2 / g.
[0092] Comparative Example 3
[0093] In this comparative example: in the positive electrode sheet, the positive electrode active material includes 30% LiMn 0.6 Fe 0.4 PO4 with 70% LiNi 0.8 Co 0.1 Mn 0.1 O2; in the negative electrode sheet, the negative electrode active material is graphite; the electrolyte in the electrolyte is LiPF6; the separator adopts a 9+2+2 separator (that is, the thickness of the base film is 9μm, and the boehmite coating on both sides of the base film is 2μm). The positive electrode sheet, the negative electrode sheet, the electrolyte and the separator are assembled to obtain a 20Ah lithium-ion battery.
[0094] Among them, LiMn 0.6 Fe 0.4 The median particle size of PO4 is 1.5 μm and the specific surface area is 22 m 2 / g,LiNi 0.8 Co 0.1 Mn 0.1 The median particle size of O2 is 10 μm and the specific surface area is 0.8 m 2 / g.
[0095] The gram capacity and safety performance tests were performed on the batteries assembled in Examples 1-3 and Comparative Examples 1-3. The gram capacity test process was as follows: at 25°C, the battery was charged to 4.2V at a current of 0.2C, and then discharged to 2.5V at a current of 0.2C for testing. Safety performance includes thermal runaway test and overcharge test. The method of thermal runaway test is as follows: according to the method of GB 38032-2020, after charging the test object to 100% SOC, continue to charge the test object with a 1C rate charging current for 12 minutes; immediately start the heating device and continue to heat the test object at its maximum power. When thermal runaway occurs or the temperature of the monitoring point reaches 300°C, stop triggering and turn off the heating device; during the heating process and within 1 hour after the end of heating, if a fire or explosion occurs, the test is terminated; the method of overcharge test is as follows: according to the method of national standard GB 38032-2020, the battery is fully charged to 4.2V in a constant current and constant voltage manner, and then charged to 4.62V or 115% SOC at a current constant current of 1C rate, and then charging is stopped. The test results are shown in Table 1 and Figure 1-Figure 3 As shown:
[0096] Table 1 Gram capacity and safety performance test results of different embodiments and comparative examples
[0097]
[0098] The positive electrode active materials in Examples 1-3 and Comparative Examples 1-3 are composed of lithium iron manganese phosphate and lithium nickel cobalt manganese oxide in different proportions, wherein the added mass ratios of lithium nickel cobalt manganese oxide in Examples 1-3 and Comparative Examples 1-3 are 10%, 30%, 50%, 0%, 60% and 70%, respectively. As can be seen from Table 1, as the addition ratio of lithium nickel cobalt manganese oxide in the positive electrode active material increases, the gram capacity of the battery also gradually increases. The gram capacity directly affects the energy density of the battery. The higher the gram capacity, the higher the battery energy density. However, as the addition ratio of lithium nickel cobalt manganese oxide in the positive electrode active material increases, the maximum temperature of thermal runaway also gradually increases, and the time of thermal runaway becomes shorter and shorter, indicating that the thermal safety performance of the battery is weakened as the addition ratio of lithium nickel cobalt manganese oxide in the positive electrode active material increases. Therefore, in order to enable the battery to take into account both high energy density and high safety performance, it is necessary to control the mass ratio of lithium iron manganese phosphate and lithium nickel cobalt manganese oxide in the positive electrode active material within a certain range.
[0099] It can be seen from the test results of Examples 1-3 and Comparative Example 1 that when the mass proportion of lithium nickel cobalt manganese oxide in the positive electrode active material formed by the compounding of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide does not exceed 50%, the maximum temperature of thermal runaway is within 600°C, the start time of thermal runaway exceeds 1400s, and no fire or explosion occurs after thermal runaway; when the overcharge test is performed, the battery does not catch fire or explode. This shows that when the mass proportion of lithium nickel cobalt manganese oxide in the positive electrode active material formed by the compounding of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide is within 50%, the battery safety performance is high and can meet the battery safety standards. In addition, since the positive electrode active materials of Examples 1-3 include both lithium manganese iron phosphate and lithium nickel cobalt manganese oxide, the gram capacity of the battery is significantly higher than that of the positive electrode active material of Comparative Example 1, which only includes lithium iron manganese phosphate. That is to say, in Examples 1-3 of the present application, by including both manganese iron phosphate and lithium nickel cobalt manganese oxide in the positive electrode active material and controlling the ratio between the two within a certain range, the battery can have both high energy density and high safety performance.
[0100] Among them, the thermal runaway test curves of Example 2, Comparative Example 1 and Comparative Example 2 are respectively as follows: Figure 1 , Figure 2 and Figure 3 shown. Figure 1 The thermal runaway test curve of the positive electrode active material is 70% LMFP + 30% NCM (Example 2), the thermal runaway start time is 1417s, and the thermal runaway maximum temperature is 515°C; Figure 2 This is the thermal runaway test curve of the positive electrode active material being pure LMFP (Comparative Example 1), the thermal runaway start time is 1479s, and the thermal runaway maximum temperature is 468°C; Figure 3 The thermal runaway test curve of the positive electrode active material is 40% LMFP + 60% NCM (Comparative Example 2), and the thermal runaway start time is 1282s, and the maximum thermal runaway temperature is 671°C. Comparative analysis shows that when the positive electrode active material is pure LMFP, the time for the thermal runaway to start is the longest, the temperature is the lowest when the thermal runaway occurs, and there is no fire or explosion during the process, indicating that pure LMFP has the highest thermal stability. As the mass of the ternary compounded in LMFP increases, the time for the thermal runaway to start becomes shorter, and the maximum temperature of the thermal runaway becomes higher, indicating that as the amount of the ternary compounding increases, the thermal stability of the compounded material system deteriorates. Figure 3 When the NCM content was 60%, fire occurred during the thermal runaway test, indicating that the amount of compound ternary should not be too high, as too high a content may cause obvious safety problems.
[0101] It can be seen from the test results of Examples 1-3 and Comparative Examples 2-3 that when the mass proportion of lithium nickel cobalt manganese oxide in the positive electrode active material formed by the compounding of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide is 60%, the maximum temperature of thermal runaway reaches 671°C, and fire occurs after thermal runaway occurs, and when the mass proportion of lithium nickel cobalt manganese oxide is 70%, the maximum temperature of thermal runaway is 793°C, the time of thermal runaway occurs faster, and fire and explosion occur after thermal runaway occurs. And the battery overcharge test in Comparative Examples 2-3 cannot pass. It can be seen from the above test results that when the mass proportion of lithium nickel cobalt manganese oxide in the positive electrode active material formed by the compounding of lithium manganese iron phosphate and lithium nickel cobalt manganese oxide exceeds 50%, although the gram capacity of the battery is increased and the energy density is increased, the battery safety drops sharply. In order to ensure the safety of the battery, the mass proportion of lithium nickel cobalt manganese oxide in the positive electrode active material does not exceed 50%.
[0102] In addition, the rate discharge performance test was conducted on the batteries in Examples 1-3 and Comparative Example 1. The test method is as follows: Rate performance: At 25°C, the battery was charged to 4.2V with a current of 0.5C, and then discharged to 2.5V at different rates. Figure 4 As shown:
[0103] from Figure 4 It can be seen that when the proportion of lithium nickel cobalt manganese oxide in the positive electrode active material is controlled below 50%, the rate discharge performance of the battery is basically the same. This shows that the addition of lithium nickel cobalt manganese oxide can ensure the safety performance of the battery and maintain a certain high energy density, but will not affect other properties of the battery such as rate discharge performance.
[0104] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A positive electrode active material, characterized in that: Including lithium iron manganese phosphate and lithium nickel cobalt manganese oxide; Wherein, the mass ratio of the lithium manganese iron phosphate to the lithium nickel cobalt manganese oxide is (50-95): (5-50); The general chemical formula of the lithium nickel cobalt manganese oxide is: LiNi a Co b Mn (1-a-b) O2, 0.6≤a<1, 0<b<0.5, 0<a+b<1.
2. The positive electrode active material according to claim 1, characterized in that The median particle size D50 of the lithium manganese iron phosphate is 0.5 μm-5 μm, and the specific surface area is 14 m 2 / g-25m 2 / g.
3. The positive electrode active material according to claim 1, characterized in that The median particle size D50 of the lithium nickel cobalt manganese oxide is 4 μm-18 μm, and the specific surface area is 0.2 m 2 / g-1.5m 2 / g.
4. The positive electrode active material according to claim 3, characterized in that The chemical formula of the lithium iron manganese phosphate is LiMn 0.6 Fe 0.4 PO4; And / or, the chemical formula of the lithium nickel cobalt manganese oxide is LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.7 Co 0.1 Mn 0.2 O2 and LiNi 0.9 Co 0.05 Mn 0.05 At least one of O2.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The mass ratio of the lithium manganese iron phosphate to the lithium nickel cobalt manganese oxide is 90:
10.
6. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The mass ratio of the lithium manganese iron phosphate to the lithium nickel cobalt manganese oxide is 70:
30.
7. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The mass ratio of the lithium manganese iron phosphate to the lithium nickel cobalt manganese oxide is 50:
50.
8. A positive electrode slurry, characterized in that: The invention comprises the positive electrode active material as claimed in any one of claims 1 to 7.
9. The positive electrode slurry according to claim 8, characterized in that: Also includes a positive electrode conductive agent, a positive electrode binder and a positive electrode dispersant; Wherein, the mass ratio of the positive electrode active material, the positive electrode conductor, the positive electrode binder and the positive electrode dispersant is (95-98): (0.5-2.5): (1-3): (0-1).
10. The positive electrode slurry according to claim 9, characterized in that: The positive electrode conductive agent includes at least one of carbon nanotubes, graphene and acetylene black; And / or, the positive electrode binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid.
11. A positive electrode sheet, characterized in that: It comprises a positive electrode foil and a positive electrode active layer coated on the positive electrode foil; Wherein, the positive electrode active layer is prepared by using the positive electrode slurry as described in any one of claims 8 to 10, or, The positive electrode active layer comprises the positive electrode active material according to any one of claims 1 to 7.
12. The positive electrode sheet according to claim 11, characterized in that: The positive electrode foil is a carbon-coated aluminum foil; The carbon-coated aluminum foil comprises an aluminum foil and a carbon coating layer coated on the aluminum foil, wherein the thickness of the aluminum foil is 6 μm-20 μm, and the thickness of the carbon coating layer is greater than 0 μm and less than or equal to 1 μm.
13. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 11 or 12.
14. A vehicle, characterized in that: Comprising the battery of claim 13.
Citation Information
Patent Citations
Lithium ion battery anode slurry, anode and battery
CN102237521A
Lithium ion battery positive active substance, anode material, anode material sizing agent, anode piece, preparation method and lithium ion battery
CN107528050A
Lithium ion battery positive electrode material, lithium ion battery positive pole plate and lithium ion battery
CN107565094A
Cathode active material, secondary battery and preparation method
CN116504961A
Positive plate, preparation method thereof and battery
CN119208538A
Cited By
Positive pole piece of large soft package battery cell, preparation method of positive pole piece, large soft package battery cell and plant protection unmanned aerial vehicle
CN120637383A
Positive pole piece of lithium ion battery, preparation method of positive pole piece and lithium ion battery
CN121662727A
Positive electrode active material, positive electrode slurry, positive electrode sheet, battery, and vehicle
WO2026081388A1
Positive electrode material for lithium-ion battery, and positive electrode and lithium-ion battery comprising same
WO2026179577A1